2005
DOI: 10.1111/j.1542-4758.2005.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transfusion‐transmitted virus infection in patients on maintenance hemodialysis from New Delhi, India

Abstract: Transfusion-transmitted virus (TTV) has been reported from a number of hemodialysis (HD) units from various countries throughout the world. TTV has been associated with liver diseases, viral hepatitis B, and C. Clinical details and information regarding TTV prevalence from India are insufficient. The prevalence and clinical significance of TTV infection were studied in New Delhi, India in HD patients. Serum samples were derived from 75 patients on maintenance HD, and 75 age- and sex-matched voluntary blood don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
3
28
1
2
Order By: Relevance
“…Asim et al 4 reported TTV-DNA in 45.3% volunteer blood donors whereas rate of TTV-DNA infection reported by Chattopadhyay et al 5 was 83% in patients on HD in New Delhi. The clinical background, age, sex, duration of HD and ALT levels did not differ significantly between TTV DNApositive and negative HD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Asim et al 4 reported TTV-DNA in 45.3% volunteer blood donors whereas rate of TTV-DNA infection reported by Chattopadhyay et al 5 was 83% in patients on HD in New Delhi. The clinical background, age, sex, duration of HD and ALT levels did not differ significantly between TTV DNApositive and negative HD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Over many years, hepatitis was the main cause of transfusion-associated chronic disease, liver cirrhosis, hepatocellular carcinoma, and death (Chattopadhyay et al 2005). Since 1993, the screening of blood donors for HBV and HCV infection became obligatory in Brazil as part of the HIV control program, leading to a tighter control of blood samples used in transfusion (Gonçales Junior 1998).…”
mentioning
confidence: 99%
“…Hemodiyaliz hastalarında hepatite neden olan hepatit E (HEV), Hepatit G (HGV) , transfüzyonla bulaşan virus (TTV) viruslerinin sıklığına ilişkin çeşitli çalışmalar yapılmıştır ve Transfusion transmitted virus (TTV)'un bulaş yolu tam olarak aydınlatılamasa da, hemodiyaliz hastalarında TTV seroprevalansı %9,3-83 arasında değişmektedir [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionunclassified